2007
DOI: 10.1007/s10834-007-9074-7
|View full text |Cite
|
Sign up to set email alerts
|

Linking Financial Strain to Marital Instability: Examining the Roles of Emotional Distress and Marital Interaction

Abstract: Using a sample consisting of 4,997 married couples from the National Survey of Families and Households, individual emotional distress, the occurrence of couple disagreements, couple fighting, and couple quality time together mediated the relationship between financial strain and personal assessments of marital instability. The overall results suggest that financial strain influences both positive and negative forms of couple interaction which are stronger mediators than personal emotional distress of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 34 publications
14
125
0
1
Order By: Relevance
“…Research on first marriages has suggested that the relationship between financial strain and marital quality is influenced by the affective quality of marital relations (Conger et al, 1990) and mediated by couple interaction forms (i.e. disagreements, fighting, quality time together; see Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007). Economic pressure appears to increase the risk for hostility and diminished emotional warmth in marriage, and these individual/interpersonal conditions, in turn, increase the risk for marital conflict and subsequent marital distress (Conger, Reuter, & Elder, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Research on first marriages has suggested that the relationship between financial strain and marital quality is influenced by the affective quality of marital relations (Conger et al, 1990) and mediated by couple interaction forms (i.e. disagreements, fighting, quality time together; see Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007). Economic pressure appears to increase the risk for hostility and diminished emotional warmth in marriage, and these individual/interpersonal conditions, in turn, increase the risk for marital conflict and subsequent marital distress (Conger, Reuter, & Elder, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…There are few family finance research articles with marital instability as an outcome variable (Dew, 2016). That being said, lack of financial resources, as well as other financial stressors, do predict marital dissatisfaction (Archuleta et al, 2011;Conger, Rueter, & Elder, 1999;Dew, 2011;Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007) and divorce (Dew, 2009;cf. Andersen, 2005).…”
Section: Literature Review Empirical Reviewmentioning
confidence: 99%
“…The model whereby negative economic events lead to economic pressure, then worse affective states, and finally declines in marital quality is termed the family stress model of economic pressure and marital distress, or simply the family stress model (Conger & Elder, 1994). In addition to validating the family stress model using U.S. nationally-representative data (Dew, 2007;Gudmunson et al, 2007), researchers have validated the family stress model across countries and cultures (Kinnunen & Pulkkinen, 1998;Kwon, Rueter, Lee, Koh, & Ok, 2003). This study uses the family stress model as the main framework of this study.…”
Section: The Family Stress Model: Economic Reversal and Relationshipmentioning
confidence: 99%
“…Further, this study is among one of few to examine how actual financial management behaviors are associated with relationship quality. Most studies in this area (e.g., Dew, 2007;Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007) use actual financial well-being, such as assets or negative financial events. Finally, this is one of the first studies to test whether sound financial management behaviors mediate and/or moderate the relationship between financial declines and relationship happiness.…”
mentioning
confidence: 99%